Visual analysis of material flow during friction stir welding of nylon-6 - Zafar, A. (Asian Research Publishing Network, 2016)
Material flow during friction stir welding (FSW) is a challenging subject that should be studied to understand the defects produced during the process. Recent achievement of friction stir welding of polymers, necessitates the study of this process on polymers as well. In this paper material flow was studied on nylon-6 due to its wide engineering applications. For this purpose, a 1.5 mm thin polymer sheet, different in color, was used as a marker material and embedded in nylon-6 at various positions. Post-weld specimens, welded at optimum friction stir welding parameters, were cut at different sections for visual analysis of flow. Results showed that flow behavior in polymers is remarkably different from metals. Flow was limited to the pin influenced zone and no flow across this zone was seen. Uniform stirring and interesting phenomenon of far off displacement of plasticized material, even out of pin diameter range was observed. Analysis also revealed the upward vertical motion of the marker material. Â© 2006-2016 Asian Research Publishing Network (ARPN).